Land conflict hot spots in Kiteto, Kilindi, Mvomero and Chalinze landscape - Kalenzi, Deus (International Livestock Research Institute, 2018)
Map showing villages that had hot spot areas for land-based conflicts in 2018 in the districts of Chalinze, Kiteto, Kilindi, and Mvomero, Coastal (Pwani), Morogoro, Tanga and Manyara regions in Tanzania.